Cystobactamids: Myxobacterial Topoisomerase Inhibitors Exhibiting Potent Antibacterial Activity1. Issue 52 (15th December 2014) - Baumann, Sascha; Herrmann, Jennifer; Raju, Ritesh; Steinmetz, Heinrich; Mohr, Kathrin I.; Hüttel, Stephan; Harmrolfs, Kirsten; Stadler, Marc; Müller, Rolf
Abstract The development of new antibiotics faces a severe crisis inter alia owing to a lack of innovative chemical scaffolds with activities against Gram‐negative and multiresistant pathogens. Herein, we report highly potent novel antibacterial compounds, the myxobacteria‐derived cystobactamids 1–3, which were isolated from Cystobacter sp. and show minimum inhibitory concentrations in the low μg mL−1 range. We describe the isolation and structure elucidation of three congeners as well as the identification and annotation of their biosynthetic gene cluster. By studying the self‐resistance mechanism in the natural producer organism, the molecular targets were identified as bacterial type IIa topoisomerases. As quinolones are largely exhausted as a template for new type II topoisomerase inhibitors, the cystobactamids offer exciting alternatives to generate novel antibiotics using medicinal chemistry and biosynthetic engineering.